Improving the Cost Effectiveness of Small Schools. Commonwealth Pacific Regional Workshop (Auckland, New Zealand, November 19-26, 1986). Final Report - Commonwealth Secretariat, London (England).; Commonwealth Secretariat, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This document summarizes the deliberations of the Commonwealth Pacific Regional Workshop, which focused on the cost effectiveness of small schools. Advantages of small schools include equity for disadvantaged groups, opportunities for rural development, preservation of cultural traditions, and the potential for educational advantages. One task force identified the need for increased parental involvement in small schools. School consolidation is an unpopular method of cutting school costs. The main costs elements in establishing and operating a small school are capital costs, salaries, maintenance, teaching supplies, boarding costs, and transportation. Small schools can be made more cost effective by streamlining the curriculum, engaging in multigrade teaching, using support services, training teachers for the unique demands of small schools, using community resources, improving supervision, boarding students, using mobile laboratories, using mobile teachers, and staggering school enrollment. Alternatives to small schools are home schooling, central schools, combined elementary and secondary schools, distance education, correspondence education, and school clusters. Participants proposed recommendations for education authorities, training institutions, and the Commonwealth Secretariat. The appendices include names of participants, a program for the workshop, titles of working papers commissioned for the workshop, a list of background papers available during the workshop, and a list of task force topics. (KS)
ERIC Note: Some pages contain light print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Involvement; Consolidated Schools; Cost Effectiveness; Curriculum Development; Educational Finance; Educationally Disadvantaged; Elementary Secondary Education; Foreign Countries; Multigraded Classes; Parent Participation; Rural Schools; Small Schools; Teaching Methods; Commonwealth of Nations; New Zealand -- Pacific Region; Collected Works, Proceedings